Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Warkop Sutara Sukamulya Tangerang Selatan - Zai, Wileni; Amirudin Amirudin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The purpose of this study was to determine the role of Price (X1) and Product Quality (X2) on Consumer Purchasing Decisions (Y) at Warkop Sutara Sukamulya Tangerang Selatan. The method used in this study is quantitative with a quantitative descriptive approach and the population in this study was 97 consumers. The sampling technique used was proportional random sampling using a questionnaire technique method with a sample of 97 respondents. The analysis tool used was Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test), Simple Linear Regression Analysis Test, Multiple Linear Analysis Test, Coefficient Analysis Test, Determination Coefficient Test, Hypothesis Test and Simultaneous Test. The results of the Price variable significantly influenced the Purchasing Decision with a t-count value of 1.824> t-table 1.661 and a Sig. value <0.05 (0.000 <0.05). The results of the Product Quality variable on Purchasing Decisions with a t count of 2.715> t table 1.661 and a Sig. value <0.05 (0.000 <0.05). The results of the Price and Product Quality variables simultaneously have a significant effect on purchasing interest with a f count of 3.910> 3.09 and a Sig. value <0.05 (0.000 <0.05). The results of the study concluded that there was a positive and significant influence both partially and simultaneously between the role of Price and Product Quality on Consumer Purchasing Decisions at Warkop Sutara Sukamulya Tangerang Selatan Keywords: Price, Product Quality, and Purchasing Decisions